Neurological patients and their lower limb orthotics: An observational pilot study about acceptance and satisfaction. (February 2017) - Swinnen, Eva; Lafosse, Christophe; Van Nieuwenhoven, Johan; Ilsbroukx, Stephan; Beckwée, David; Kerckhofs, Eric
Background: Although an orthotic device of the lower limb improves the functionality of neurological patients, anecdotally clinical experience suggests that the compliance is rather limited. Objectives: The aim was to determine the satisfaction and acceptance of a lower limb orthotic device. Study design: A qualitative observational pilot study with a mix-method design. Methods: Adult neurological patients who had a prescribed lower limb orthotic device were included. One published and clinically used questionnaire about satisfaction (D-Quest) and one ad hoc constructed questionnaire about acceptance of the orthotic device (MIRAD-ACCORT questionnaire) were used for data collection. Results: In total, 33 patients participated (28 ankle–foot orthotic device, 3 knee–ankle–foot orthotic device and 2 other types). In general, they were satisfied about their orthotic device and the services. Less than one-fourth of the patients had some negative comments about the 'visual aspects' and the 'ability to hide' of their orthotic device. These, however, had a lower priority when compared with functionality, which was reported as a main advantage and is a reason for continuing the use of their orthotic device. Conclusion: Patients were satisfied in relation to their lower limb orthotic device. With regard to acceptance, it can be concluded that factors associated with functionality and comfort are more important than the aesthetic and psychological aspects of the orthotic device. Clinical relevance: Patients were satisfied with their lower limb orthotic device. Some patients had some negative comments about the 'aesthetics aspects' and the 'ability to hide' their orthotic device. However, improvements in functionality were mostly reported as a main advantage and a reason for continuing the use of their orthotic device.